Low frequency noise in HEMT structure - Han, IK; Lee, JI; Brini, J; Chovet, A (KOREAN PHYSICAL SOC, 2001)
A comprehensive model for low frequency excess noise in HEMT structure is presented. The model includes number fluctuation mechanisms such as thermal activation, tunneling and random walk involving bulk traps and interface traps. For the gate current noise these traps contribute to the current fluctuation through barrier height modulation. Gate current flows through two Schottky barriers, one at the gate metal and the other near the two-dimensional carrier channel. Based on different noise generation mechanisms for Schottky barrier structure, we developed a novel and comprehensive model for low frequency noise in the gate current of HEMT structure. The model explains well the experimental results including the current dependence of the noise spectral density. The drain current noise is also modeled utilizing these three mechanisms, and the previously proposed effective density of traps could be translated into actual bulk trap density and interface states density. Low frequency noise is important for microwave device performance Since it can be up-converted into the microwave range and dominates the phase noise of oscillators and mixers. Low frequency noise measurements also can provide a spectroscopy tool for defects involved and complement others such as DLTS.
Keywords: SI SCHOTTKY DIODES; GATE CURRENT NOISE; RANDOM-WALK; 1/F NOISE; FLUCTUATIONS; TRANSISTORS; ELECTRONS; INTERFACE